2022
DOI: 10.3390/app12147253
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Enabled 3D Body Measurement Estimation Using Hybrid Feature Selection and Bayesian Search

Abstract: The 3D body scan technology has recently innovated the way of measuring human bodies and generated a large volume of body measurements. However, one inherent issue that plagues the use of the resultant database is the missing data usually caused by using automatic data extractions from the 3D body scans. Tedious extra efforts have to be made to manually fill the missing data for various applications. To tackle this problem, this paper proposes a machine learning (ML)-based approach for 3D body measurement esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…According to Jaeschke et al [ 2 ], in order to improve the measurement of human body parameters (length, circumference of the trunk, hips, or other body parts), scanners visualizing a three-dimensional human model may prove useful. Liu et al [ 13 ] stated that 3D scanners have fundamentally changed the approach to this type of anthropometric measurement in recent years. In [ 14 ], a synthetic data set of human body shapes was used to develop a method for estimating anthropometric parameters using deep learning and neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…According to Jaeschke et al [ 2 ], in order to improve the measurement of human body parameters (length, circumference of the trunk, hips, or other body parts), scanners visualizing a three-dimensional human model may prove useful. Liu et al [ 13 ] stated that 3D scanners have fundamentally changed the approach to this type of anthropometric measurement in recent years. In [ 14 ], a synthetic data set of human body shapes was used to develop a method for estimating anthropometric parameters using deep learning and neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…These relationships were then used to predict and adjust the pattern parameters, achieving pattern adaptability. Liu et al [16] proposed a machine learning framework that combines hybrid feature selection and a Bayesian search to estimate missing 3D body measurements, addressing the challenge of incomplete data in 3D body scanning. The study found that this approach leverages hybrid feature selection and the Bayesian search to enhance the performance of random forest (RF) and XGBoost 0.72, particularly in filling in missing data, where RF outperforms XGBoost.…”
Section: Introductionmentioning
confidence: 99%